Designing a Sports Event Management Model with an Artificial Intelligence Approach - Hajighiasian, Fahimeh; Hamidi, Mehrzad; Sajjadi, Seyed Nasrollah (AI and Tech in Behavioral and Social Sciences, 2024)
In recent years, artificial intelligence (AI) has demonstrated its superiority across various domains within the broad spectrum of sports event management, leading to an increased adoption of AI in the sports industry. AI is now the subject of the most precise and in-depth research conducted globally. Therefore, this study aims to identify the essential factors of social acceptance of artificial intelligence (AI) in the field of sports event management and to design a sports event management model with an AI approach. Given that the data used in this research for importance weighting, refinement, classification, and determining the relationships between model components were derived from a persuasive Delphi survey of experts in the model design section, and for validating the proposed model, a questionnaire survey tool was used with stakeholders and responsible parties, the type of research in terms of the design used is survey-based. Ultimately, in the present study, a judgmental survey approach was employed for importance weighting and data refinement, and then the data were quantified based on fuzzy logic and utilized multi-criteria quantitative approaches. Thus, the overall method or type of research in terms of the nature and type of data and methods used is of the "mixed method" type. In this research, based on previous studies, the relationship between social acceptance or successful application of AI technologies as a dependent variable and organizational will, senior management inclination, compatibility and adaptability, government support, competitive pressure, and relative advantage as explanatory variables were examined. According to the results obtained, among the main factors influencing social acceptance or the successful application of AI technologies in the field of sports event management in Iran, the priorities are as follows: 1. Senior management inclination, 2. Relative advantage, 3. Organizational will, 4. Competitive pressure, 5. Compatibility and adaptability, and 6. Government support. AI will become an integral part of every institution worldwide in the long term; using AI in sports event management is not a trend but a scientific necessity.